Coal Fly Ash Ceramics: Preparation, Characterization, and Use in the Hydrolysis of Sucrose. (3rd July 2014) - dos Santos, Ricardo Pires; Martins, Jorge; Gadelha, Carlos; Cavada, Benildo; Albertini, Alessandro Victor; Arruda, Francisco; Vasconcelos, Mayron; Teixeira, Edson; Alves, Francisca; Lima Filho, José; Freire, Valder
Abstract : Coal ash is a byproduct of mineral coal combustion in thermal power plants. This residue is responsible for many environmental problems because it pollutes soil, water, and air. Thus, it is important to find ways to reuse it. In this study, coal fly ash, obtained from the Presidente Médici Thermal Power Plant, was utilized in the preparation of ceramic supports for the immobilization of the enzyme invertase and subsequent hydrolysis of sucrose. Coal fly ash supports were prepared at several compaction pressures (63.66–318.30 MPa) and sintered at 1200°C for 4 h. Mineralogical composition (by X-ray diffraction) and surface area were studied. The ceramic prepared with 318.30 MPa presented the highest surface area (35 m 2 /g) and amount of immobilized enzyme per g of support (76.6 mg/g). In assays involving sucrose inversion, it showed a high degree of hydrolysis (around 81%) even after nine reuses and 30 days' storage. Therefore, coal fly ash ceramics were demonstrated to be a promising biotechnological alternative as an immobilization support for the hydrolysis of sucrose.